Análisis del parto occidental y el parto ancestral en pacientes atendidas en el Hospital Asistencial Saraguro de la provincia de Loja - Benavides Cárdenas, Amanda Gabriela (2020)
Intercultural Ecuador has consolidated the conventional health system with indigenous traditions aiming at conditions of equality, respecting its traditional customs and practices, and reducing infant maternal mortality rates being important to inform about a real alternative that empowers the mother and allows her to explore other possibilities of giving birth, in the same way, that culturally adequate childbirth is correctly implemented in all hospitals in the country. This research aims to analyze western and ancestral childbirth in patients attended at the Saraguro Assistance Hospital in the province of Loja as well as to determine its prevalence, identify the techniques used, characterization and complications. A quantitative, retrospective, cross-sectional study, with a sample of 466 patients (290 ancestral and 176 westerns) who met the inclusion criteria, the technique used is the recording and observation of medical records. The results, in terms of prevalence: ancestral delivery 62.2% and western 37.8%; within the techniques used for total users who chose the ancestral delivery is evidenced that 32.17% chose technique knees, on the other hand, in the western part, lithotomy occurs (37.8%); in respect of complications, it is observed that both ancestral and western births do not present relevant complications with 42.5% and 28.5% respectively. However, in both types of delivery, lower percentages of tearing are present, followed by fetal distress and placental retention. In conclusion, the majority of users prefer ancestral delivery since they present fewer complications concerning western delivery. Keywords: lithotomy, techniques, complications, humanized childbirth, intercultural.